THE INFLUENCE OF KURIKULUM MERDEKA ON THE UNDERSTANDING OF EDUCATIONAL CONCEPTS OF GRADE IV STUDENTS OF SDN 71 PALEMBANG - Zahratul Jamilah; Jayanti; Ida Suryani (Universitas PGRI Palembang, 2024)
This study aims to determine the effect of Merdeka Curriculum learning on understanding the concept of education for fourth grade students of SD Negeri 71 Palembang. The Merdeka Curriculum is expected to increase student involvement and creativity in learning, especially in subjects that are often considered boring and theoretical. The method used in this research is a quantitative experiment with a pretest-posttest control group design. The research sample consists of two groups, namely the experimental group taught using the Merdeka Curriculum approach and the control group using conventional learning. Data were collected through multiple choice tests that measured students' understanding of the principles of Pancasila and citizenship. The results showed that learning with the Merdeka Curriculum had a significant effect on student understanding, with a t_count value of 12.430 which is greater than the t_table of 2.015. This study concludes that the application of Merdeka Curriculum can improve students' understanding of the concept of Citizenship, especially in understanding bad behavior in oneself and the environment.